KOMPARASI SEJARAH DAN ANALISIS TEKS SABINE SCHMIDTKE (Program Studi Aqidah dan Filsafat Islam Fakultas Ushuluddin dan Pemikiran Islam, 2022)
This study looks at the numerous studies of Islamic theology conducted by Western nations since the early nineteenth century. They studied Muslim thinkers' writings and brought them to the West. Initially, the study of the manuscript was general in nature, but later thinkers narrowed it down to a specific study. Sabine Schmidtke is a modern Orientalist who specializes in manuscripts of Islamic theology, particularly Mu'tazilah theology. In this study, the author employs the library research method to examine Sabine Schmidtke's books and journals on the relationship between Jewish Karaites, Shia theology and Mu'tazilah theology. Based on the author's research, Sabine's comparative historical and textual studies have revealed that the Shia school of thought and the Jewish Karaites sect have adopted Mu'tazilah thought, specifically the thought of Abu al-Husayn al-Basri. They not only adopted ideas, but they also copied and preserved writings found in Yemen in the form of manuscripts. Keywords: Sabine Schmidtke, Jewish Karaites, Mu'tazilah.